2009
DOI: 10.7326/0003-4819-150-6-200903170-00004
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Testing, Clinical Outcomes, and Health Services Use in Emergency Department Patients With Dyspnea

Abstract: Janssen-Cilag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 23 publications
1
35
1
4
Order By: Relevance
“…Despite a difference in admission rate among subgroups, probably reflecting symptom severity, we observed no difference in admission rate by blinding within subgroups. Hence, in the present setup, availability of test results did not affect the decision to admit these symptomatic patients, as observed also in the IMPROVE-CHF study 7 and by Schneider et al 14 Both these studies demonstrated similar admission rates to those in the present study, in contrast to a possible reduction reported in a recent relatively large meta-analysis. 15 This neutral finding could plausibly be the result of central laboratory testing involving a necessary turnaround time.…”
Section: Diagnosis Of Adhf In the Edcontrasting
confidence: 56%
“…Despite a difference in admission rate among subgroups, probably reflecting symptom severity, we observed no difference in admission rate by blinding within subgroups. Hence, in the present setup, availability of test results did not affect the decision to admit these symptomatic patients, as observed also in the IMPROVE-CHF study 7 and by Schneider et al 14 Both these studies demonstrated similar admission rates to those in the present study, in contrast to a possible reduction reported in a recent relatively large meta-analysis. 15 This neutral finding could plausibly be the result of central laboratory testing involving a necessary turnaround time.…”
Section: Diagnosis Of Adhf In the Edcontrasting
confidence: 56%
“…14 -18 Mueller et al 24 showed that in Switzerland, patients who had BNP testing in the ED had earlier initiation of appropriate treatment, decreased hospital and intensive care unit admission rates, earlier discharge, and decreased cost of treatment. In contrast, the randomized controlled trial BNP in Shortness of Breath (SOB) study conducted in Australia by Schneider et al 25 showed that BNP testing in dyspneic patients presenting to the ED did not improve hospital admission rates, length of hospital stay, or management in the ED.…”
Section: Clinical Perspective On P 110mentioning
confidence: 73%
“…This can expedite evaluation and initiation of appropriate treatment and may contribute to reduced costs and length of stay for those who require hospitalization (207,208). Routine use of BNP in all patients presenting with acute dyspnea is not recommended (209), especially when admission is highly likely in any event (209). In acute care settings such as an ED, the sensitivity of BNP or NTproBNP is substantially higher than its specificity, and its utility is greatest for ruling out heart failure as a cause of acute dyspnea in patients with a low to intermediate pretest probability of heart failure (210,211).…”
Section: Evaluation and Treatment Evaluationmentioning
confidence: 99%